Comparison between hepaticojejunostomy and hepaticoduodenostomy after excision of choledochal cyst in children: a cohort study - Johann Paulo Suico Guzman; Leandro L Resurreccion III; Marcus Lester R Suntay; Renato G Bernaldez (BMJ Publishing Group, 2019)
Objective Hepaticojejunostomy (HJ) and hepaticoduodenostomy (HD) are commonly used biliary reconstruction techniques after choledochal cyst excision. HD has been suggested to be a more physiologic alternative during reconstruction. The objective of this study is to compare operative time, hospital stay, morbidity (leak, cholangitis, ileus, and obstruction), and mortality between HJ and HD after cyst excision.Methods This is a 14-year retrospective cohort study of pediatric patients (≤18 years old) who underwent choledochal cyst excision and subsequent biliary reconstruction at the Philippine Children's Medical Center. Data were taken from inpatient charts, operative technique, OPD logbook, readmission, and OPD charts.Results There were 122 patients: 56% HD and 44% HJ. Majority were female (72%), with 1:2.6 male to female ratio. The average age was 36.1 months, with a mean follow-up of 32.8 months (range 6 months-14 years). The most common cyst was type I (87%). Operative time was longer for HJ compared with HD (321.3 vs 203.6 min; p=0.000). Hospital stay was longer with HJ compared with HD (7.7 vs 6.8 days; p=0.002). Mortality rate was low at 1.6% while morbidity was at 13.9% in both groups. Although morbidity was higher among those who underwent HD, there was no significant difference between the two procedures. Anastomotic leak (4%) and cholangitis (7.4%) were observed in HD, and ileus (7.4%) was observed in the HJ group.Conclusions In our series, HD provided less operative time and hospital stay than with HJ. We did not observe bile gastritis after HD as compared with others. It is suggested that longer follow-up is needed to confirm such findings.